Bahasa Inggris - Rika Henda Safitri; Asfeni Nurullah; Rosihan Arief HS (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2020)
The large potential of local governments to obtain very high-performance scores made researchers interested in making research on the influence audit opinion on the performance of local governments in South Sumatra.In this quantitative study, the testing method used to test the hypotheses that have been made is by using multiple linear regression test, using a testing tool that is SPSS 2.0. The population in this study is the district/city government and the regional government of South Sumatra Province. Result from this study is the South Sumatra Provincial Government's audit opinion has a significant influence on the local Government's audit performance score South Sumatera Province.